Human values and preferences for cleaner livestock production. (20th January 2016) - Caracciolo, F.; Cicia, G.; Del Giudice, T.; Cembalo, L.; Krystallis, A.; Grunert, K.G.; Lombardi, P.
Abstract: This article analyzes the relationship between the preferences of European consumers for process attributes of pig farming, broadly related to sustainable oriented practices, and the individual human values as identified by Schwartz. A sample of 2437 nationally representative individuals from five European countries was analyzed using a generalized logit model. Our contribution suggests that European consumers are aware of the environmental impact of pig production. Swine production attributes that emerged, as most significant, in our survey are those related to the possibilities of pigs being raised outdoors. Less important, bust still significant, are the positive consumers preference for low fat content, standard meat quality and small farm size. Finally, our results suggest that consumers preferences are massively linked to individual values. In particular, consumers showing enhanced "self-transcendency" and high "openness to change" values are likely to call for cleaner pork production systems. On the contrary, consumers with more pronounced "self-enhancement", "conservation" and "hedonism" values are more likely to pay little attention to sustainability in the swine sector. Results allow to assess the social acceptance of the implementation of cleaner production processes in livestock production. Highlights: We investigate how and to what extent European consumers are concerned with the sustainability of the pig industry. Relation between individual values and preferences for sustainability aspects in livestock production processes. Values and preferences for pig process attributes relationship is useful for introducing cleaner swine production processes. Our study helps to identify, among cleaner livestock practices, those mostly preferred by European consumers.